2014
DOI: 10.1371/journal.pone.0090093
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Exposure to GLP-1 Increases GLP-1 Synthesis and Release in a Pancreatic Alpha Cell Line (α-TC1): Evidence of a Direct Effect of GLP-1 on Pancreatic Alpha Cells

Abstract: Aims/HypothesisIncretin therapies, which are used to treat diabetic patients, cause a chronic supra-physiological increase in GLP-1 circulating levels. It is still unclear how the resulting high hormone concentrations may affect pancreatic alpha cells. The present study was designed to investigate the effects of chronic exposure to high GLP-1 levels on a cultured pancreatic alpha cell line.Methodsα-TC1-6 cell line was cultured in the presence or absence of GLP-1 (100 nmol/l) for up to 72 h. In our model GLP-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…In our study, we found increased proliferation of a-cells in the pancreas of rAd-GLP-1-treated mice compared with rAd-bgal-treated mice after ablation of b-cells by STZ. Similarly, we found that treatment of aTC1-9 cells, which produce glucagon but not preproinsulin mRNA (20,30), with exendin-4, a GLP-1 receptor agonist, increased the proliferation of a-cells.…”
Section: Discussionsupporting
confidence: 55%
“…In our study, we found increased proliferation of a-cells in the pancreas of rAd-GLP-1-treated mice compared with rAd-bgal-treated mice after ablation of b-cells by STZ. Similarly, we found that treatment of aTC1-9 cells, which produce glucagon but not preproinsulin mRNA (20,30), with exendin-4, a GLP-1 receptor agonist, increased the proliferation of a-cells.…”
Section: Discussionsupporting
confidence: 55%
“…Proteins were extracted from INS-1 cells with RIPA lysis buffer, and Western blotting was performed as previously described 59 . Membranes were incubated with primary antibodies (used at a final dilution 1:1000 in 5% BSA, over night at 4 °C with gentle agitation) for representative subunit of the Complexes I, IV (Thermo Fisher Scientific, Cambridge, UK), III, V (Santa Cruz Biotechnology, Santa Cruz, CA, USA) and for coenzyme Q10 (Abcam, Cambridge, UK) and then exposed to anti-rabbit, anti-mouse (GE Healthcare Life Sciences, Little Chalfont, UK) or anti-goat (Santa Cruz Biotechnology) secondary antibodies (used at a final dilution 1:2000 in 5% milk, 1 hour at room temperature with gentle agitation), conjugated to horseradish peroxidase.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, there is little consensus regarding whether GLP-1R is expressed in glucagon-producing a-cells located in pancreatic islets. Some studies show no GLP-1R protein or mRNA expression in a-cells of normal mice (7), some show GLP-1R is expressed in a small portion of a-cells in adult mice (8,9), and others show clear GLP-1R expression in a-cells, especially during early development and throughout life in mice with a-cell hyperplasia (10,11). To make the topic even more complicated, studies have reported that the commonly used anti-GLP-1R antibodies are neither specific nor sensitive enough to reliably detect GLP-1R expression in tissues (1,12).…”
mentioning
confidence: 99%